The Fossil Record of Elateridae (Coleoptera: Elateroidea): Described Species, Current Problems and Future Prospects - Kundrata, Robin; Packova, Gabriela; Prosvirov, Alexander S; Hoffmannova, Johana (Insects, 2021)
The Elateridae (click-beetles) are the largest family in Elateroidea; however, their relationships, systematics and classification remain unclear. Our understanding of the origin, evolution, palaeodiversity and palaeobiogeography of Elateridae, as well as reconstruction of a reliable time-calibrated phylogeny for the group, are hampered by the lack of detailed knowledge of their fossil record. In this study, we summarize the current knowledge on all described fossil species in Elateridae, including their type material, geographic origin, age, bibliography and remarks on their systematic placement. Altogether, 261 fossil species classified in 99 genera and nine subfamilies are currently listed in this family. The Mesozoic click-beetle diversity includes 143 species, with most of them described from the Jurassic Karatau, and 118 described species are known from the Cenozoic deposits, mainly from the Eocene North American Florissant Formation and European Baltic amber. Available data on the described past diversity of Elateridae suggest that almost all fossil lineages in this group are in urgent need of revision and numerous Mesozoic species might belong to different families. Our study is intended to serve as a comprehensive basis for all subsequent research focused on the click-beetle fossil record.
Keywords: palaeodiversity; evolution; Eucnemidae; catalogue; classification; Mesozoic; systematics; click-beetles; Cenozoic